Health Inequalities in Indonesia’s Rural Areas: Addressing the Gap in Healthcare Access and Outcomes (Indonesian Health Justice Review, 2025)
Healthcare access and outcomes in Indonesia’s rural areas are marked by significant disparities when compared to urban centers. This paper examines the causes and consequences of these health inequalities, focusing on the barriers rural populations face in accessing essential healthcare services. Through data analysis, field surveys, and interviews with rural residents and healthcare professionals, the study explores factors such as distance to healthcare facilities, financial barriers, limited healthcare infrastructure, and cultural beliefs that affect healthcare utilization. The research reveals that rural communities experience higher rates of preventable diseases, poor maternal and child health outcomes, and limited access to specialized medical care, which contribute to overall health disparities. Despite the Indonesian government’s efforts to improve healthcare access through programs like JKN, the rural-urban health divide persists due to inadequate resources, insufficient healthcare personnel, and limited health education. The paper argues that addressing health inequalities in rural Indonesia requires targeted interventions that focus on improving healthcare infrastructure, increasing healthcare worker incentives to work in rural areas, and enhancing health literacy among rural populations. The study concludes with policy recommendations aimed at reducing these disparities and achieving greater healthcare equity for rural communities.